Het Volk and the gold mines: The debate on labour policy, 1905-1910 - Jeeves, A.H. (My University, 1980)
During the political upheavals which accompanied the shift from "Milnerism" to responsible Government in the Transvaal, the still troubled Johannesburg mining industry confronted serious new problems. In Britain, the Election of 1906 confirmed in power a hostile Liberal Party, avowedly suspicious of Randlords and determined to deny them further supplies of Chinese labour. This government planned major political initiatives in South Africa which seemed equally to jeopardize mining interests. Leaders of the Chamber of Mines were already involved in open political warfare aimed to prevent an anti-Randlord local coalition, perhaps in alliance with the Liberals, from taking power in the Colony. During the difficult years of post-war recovery after 1902, the industry had received powerful support from the Milner regime in the Transvaal and from the British Unionists.
African Studies Seminar series. Paper presented 2 June, 1980
Keywords: Mines and mineral resources. South Africa. Transvaal